“Fighting knowledge” characterization and development: contents of an integrated model for teaching martial arts and combat sports (Revista de Artes Marciales Asiáticas, 2015)
This paper aims to define the principles and technical-tactical contents that characterize the global “fighting knowledge” referring to martial arts and combat sports. From a methodological point of view, we seek to identify the praxical limits of the different martial arts and combat sports disciplines, through the analysis of the convergence points, which can provide consistency as a group of practices, and from where is possible to develop a teaching process. The principles and contents considered in this integrated perspective establish the possibilities of action, independently from institutionalized technical abilities in each combat sport. From the “fighting knowledge technical-tactical structure” we propose the development of the “fighting knowledge” and we emphasize the importance of arising the “tactical intention” of the students. The distribution and categorization of the “fighting actions” presented, try to offer tools and criteria for the martial arts and combat sports initiation process.